The Socio-Economic Consequences of Implementing Usury Ceilings in the Republic of Armenia - Gabrielyan, Tigran (Bulletin of Yerevan University G: Economics, 2022)
Usury ceilings/interest rate caps are a tool commonly used by governments to protect consumers from abusive lending practices and to prevent extreme forms of borrower exploitation by loan providers. However, numerous studies indicate that this tool can often have the opposite effect – it can make it harder for financially vulnerable individuals to obtain loans, which they rely on for food, rent, and other essential needs. Consumer loans are widespread in Armenia and the organizations that provide these loans are often criticized for exploiting borrowers and charging excessive or unfair prices. For these reasons, a bill to implement interest rate caps was proposed in 2019 but was not approved by the parliament. However, considering the high risk of “debt traps” in Armenia, it is likely that the enactment of this bill will return to the agenda of policymakers in the future. The purpose of this study is to investigate the consequences of a potential interest rate cap in Armenia and how it would affect the financial well-being of financially vulnerable individuals. Firstly, we find that interest rates, on average, are not high enough to be considered unfair or excessive taking into account the characteristics unique to “universal loan organizations” and using the interest rates of similar organizations in other countries as a guideline. Secondly, we find that the interest rate cap proposed in 2019 was lower than the market average for similar loans, which means that if this bill were to pass, access to these types of loans would significantly decline for financially vulnerable individuals, who use these loans to pay for essential needs. The study proposes that policymakers take the average market interest rate of consumer loans provided by these organizations into account and propose a usury ceiling relative to the market average. Furthermore, the use of alternative methods of consumer protection is encouraged.